Double Trouble: A Rare Case of Dual Esophageal Stenosis in a 4-month-old - Amar Shah; Ria Sharma; Anirudh Shah (Journal of Indian Association of Pediatric Surgeons)
Esophageal stenosis is an uncommon clinical condition defined as a fixed narrowing of the esophagus. It can be congenital or acquired. The incidence of congenital esophageal stenosis (CES) is 1 in 25,000–50,000 live births. Most of these patients present in early infancy and many of them require surgical intervention. We report a very interesting case of a 4-month-old child with esophageal stenosis involving two different segments of the esophagus who was successfully treated surgically. This is one of the rarest variants of CES which involves two different segments of the esophagus.